A Green and Efficient Synthesis of 3-Hydroxy-4-methoxycinnamaldehyde via a Calcium Oxide–Ethanol Heterogeneous System - Duan, Boxun; Sun, Jiangyuan; Deng, Zhan; Li, Junzhang (Synthesis, 2025)
3-Hydroxy-4-methoxycinnamaldehyde is an important organic intermediate primarily synthesized via the aldol condensation of isovanillin and vinyl acetate. Traditional synthetic processes typically employ sodium hydroxide in aqueous solution, which results in low product yields and generates large quantities of wastewater. In this study, calcium oxide is utilized as an alternative to sodium hydroxide, and the aldol condensation is carried out in anhydrous ethanol. Calcium oxide not only serves as a basic catalyst for the aldol condensation reaction but also reacts with the generated water to form calcium hydroxide, thereby removing water from the reaction system. This effectively shifts the equilibrium of the aldol condensation reaction, leading to a higher conversion rate of isovanillin and a significantly improved yield of 3-hydroxy-4-methoxycinnamaldehyde, reaching 85.2%. This study provides a novel and efficient green synthetic approach to 3-hydroxy-4-methoxycinnamaldehyde, offering significant potential for industrial applications.
Keywords: 3-hydroxy-4-methoxycinnamaldehyde; aldol condensation; calcium oxide; isovanillin; vinyl acetate